BESARNYA KONTRIBUSI TENAGA KERJA DALAM KELUARGA TERHADAP PENDAPATAN USAHATANI PADI (Oryza sativa L) SAWAH TADAH HUJAN DI DESA PASAR KAMIS KECAMATAN KERTAK HANYAR KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Wasdiyanta Wasdiyanta (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
To the effect this research is subject to be know technically paddy farming management be sighted from technical aspect. Analysing labouring effusing in family and family extern, knowing cost, acceptance and paddy farming income and to know labour contribution in family to farming income Acquired production average 4.004,80 kg / farmers or as big as 3.178,41 kg / ha (3,18 tons / ha).  Farmer acceptance in paddy farming management average as big as Rp. 20. 024. 000,00 / farmer or Rp. 15. 892. 063,49 / ha. Averagely paddy farmer earnings in once production process as big as Rp. 14. 437. 476,67 / farmers or Rp. 11. 458. 314,81 / ha On A Par gain which gotten by farmers in one season plants out is as big as Rp. 11. 110. 965,27 / farmers or on a par as big as Rp. 8. 818. 226,40 / ha. Labouring contribution in farmer family average as big as 19,10 %,